Possible reasons for the migration of tropical cyclone track over the western north pacific: Interdecadal pacific oscillation modulation - Lv, Shuo; Sun, Yuan; Zhong, Zhong; Shen, Yixuan (Frontiers in Earth Science, 2022)
Recent studies have proposed a relatively reliable metric, i.e., the annual-mean latitude of tropical cyclone (TC) lifetime maximum intensity, to evaluate the observed trend of poleward migration of TC. The documented trend in the existing records of the metric suggests that anthropogenic factors might make considerable contributions to the poleward migration of TC. However, here we show that there is no significant TC migration trend in the western North Pacific (WNP). Instead, large interdecadal variation is found in the WNP TC track over the past 35 years. Rather than the anthropogenic factors, it is the natural variability, especially the Interdecadal Pacific Oscillation (IPO), that plays a key role in modulating the migration of WNP TC track. The IPO-related TC migration is assumed to cause systematic changes (i.e., increases and decreases) in regional hazard exposure and risk. The impact of IPO on the WNP TC migration is attributed to its influences on the large-scale circulation, TC genesis potential index, and the potential intensity in the TC prevailing region of the WNP.